Penerapan Permainan Ular Tangga Sebagai Pembelajaran Pada Mata Pelajaran IPA - Mohamad Yudiyanto; Muhammad Jamil Arifillah; Peri Ramdani; Masripah, Imas (MURABBI, 2022)
This research is based on the monotony of using learning media in delivering subject matter. This raises the teacher about the impact, namely the lack of enthusiasm of student in receiving the subject matter. Meanwhile, the existence of learning media using the game snakes and ladders can answer those concern. The result of this study indicated that the use of the snake and ladder game as a learning medium in science subjects can be applied according to the design and material to be delivered, besides that student can feel a pleasant learning atmosphere, and can develop students’ attitudes towards rules, and can provide knowlage to students though the learning process of playing while learning, creating an interesting learning enverionment, providing a sense af secure and fun, developing creativity, can be used as therapy for children, develop intellectual intelligence. As for the advantages of the snake and ladder game as a learning medium, it’s very fun to do and something that is entertaining, there is active participation from students to learn, can provide direct feedback, and foster an honest and disciplined attitude in students. While the drawback required a detailed explanation of the rules and materials to be delivered.